Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1186/s40985-020-00139-0
|View full text |Cite
|
Sign up to set email alerts
|

Race against death or starvation? COVID-19 and its impact on African populations

Abstract: Background Born in the Chinese city of Wuhan, the consequences of the coronavirus pandemic on global health and economies have been and continue to be devastating. In Africa, its countries grieve for unprecedented burdens of caseloads and mortality due to COVID-19, the virus responsible for the disease. This narrative review aims to establish the scale of the health and economic crisis wrought by the pandemic in Africa, including its impact on the informal economic sector, projections of the ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 48 publications
(75 reference statements)
2
22
0
Order By: Relevance
“…Another negative impact expected from the COVID-19 pandemic could be explained by the social and political instability associated with the suspension of elections, which could trigger many political actors from opposing parity with the ruling government, generating multidimensional tensions ( 14 ). As a result, these effects further fuel societal difficulties in accessing survival requirements and lead to reduced integrity ( 15 17 ).…”
Section: Impacts Of Covid-19mentioning
confidence: 99%
“…Another negative impact expected from the COVID-19 pandemic could be explained by the social and political instability associated with the suspension of elections, which could trigger many political actors from opposing parity with the ruling government, generating multidimensional tensions ( 14 ). As a result, these effects further fuel societal difficulties in accessing survival requirements and lead to reduced integrity ( 15 17 ).…”
Section: Impacts Of Covid-19mentioning
confidence: 99%
“…COVID-19 has deepened the existing inequality in other aspects (Akseer et al, 2020), such as access to food (Kassa & Grace, 2020), education, and healthcare Molnar et al, 2021), all of which could result in higher rates of COVID-19 infection and death tolls (Shadmi et al, 2020). This may lead to a shift of vulnerable communities' resources and focus from child protection to physical survival.…”
Section: The Crucial Role Of Intersectionality In Preventing CMmentioning
confidence: 99%
“… 74 Another study in Democratic Republic of Congo revealed on how previous corruption practices by the government in response to Ebola have impacted public trust resulting into negative impacts on COVID-19 RCCE. 76 Similar cases of how distrust in government has impacted COVID-19 RCCE in Zambia, 77 Cote d’Ivoire, 78 Ghana, 79 Kenya, 80 , 81 Uganda, 81 and across other African countries 82 have been reported.…”
Section: Methodsmentioning
confidence: 65%